2016
DOI: 10.1016/j.parkreldis.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa-carbidopa intestinal gel (LCIG) treatment in routine care of patients with advanced Parkinson’s disease: An open-label prospective observational study of effectiveness, tolerability and healthcare costs

Abstract: Costs in LCIG-treated patients were stable over 3 years. LCIG treatment led to significant improvements in motor function and QoL over 18 months in LCIG-naïve patients and no worsening was observed in LCIG-experienced patients over 3 years despite natural PD progression over time. The long-term safety was consistent with the established LCIG profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
36
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 21 publications
13
36
0
7
Order By: Relevance
“…Complications with the PEG‐J tube (Devos, ; Fernandez et al., ; Nyholm et al., ) are similar to complications related to PEG for feeding purposes (Schapiro & Edmundowicz, ; Udd et al., ). The risk of peritonitis has varied between zero and 4% (Devos, ; Epstein et al., ; Lang et al., ; Palhagen et al., ), and other serious complications like colonic perforations, gastropleural fistula (Klostermann et al., ) and liver injury (Pickut et al., ), have also been described. In our material, we did not have any peritonitis, nor any need for emergency abdominal surgery due to LCIG complications.…”
Section: Discussionmentioning
confidence: 99%
“…Complications with the PEG‐J tube (Devos, ; Fernandez et al., ; Nyholm et al., ) are similar to complications related to PEG for feeding purposes (Schapiro & Edmundowicz, ; Udd et al., ). The risk of peritonitis has varied between zero and 4% (Devos, ; Epstein et al., ; Lang et al., ; Palhagen et al., ), and other serious complications like colonic perforations, gastropleural fistula (Klostermann et al., ) and liver injury (Pickut et al., ), have also been described. In our material, we did not have any peritonitis, nor any need for emergency abdominal surgery due to LCIG complications.…”
Section: Discussionmentioning
confidence: 99%
“…Management of PD requires recognition of both motor and non‐motor disturbances as well as an understanding of the relationship between these symptoms and how they can be ameliorated by medications . Treatment of NMSs can be challenging as these symptoms are often underestimated or unrecognized by clinicians and remain untreated .…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease (PD) is characterized by a combination of motor and non-motor symptoms (NMSs) underpinned by relevant neuropathological changes [1][2][3][4][5][6][7] which contribute significantly to morbidity, loss of autonomy, institutionalization and increases in healthcare costs [8,9]. The Non-Motor Symptom Scale (NMSS) and the NMS questionnaire are validated tools [10,11] to assess a broad range of NMSs and have been used in many recent PD studies [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of over 900 patients with PD and motor fluctuations initiated on LCIG indicated that the majority (~75%) of patients were able to continue long‐term LCIG to achieve improved motor function without troublesome dyskinesias even in the advanced stages of their disease . However, initiating and maintaining this form of treatment is a considerable undertaking, with the caveat that improvements in mobility may also occasionally render the patient at greater risk of falling or developing hallucinations . The costs of LCIG are substantial, but are mitigated by improvements in quality of life years (QALY) .…”
mentioning
confidence: 99%
“…2 However, initiating and maintaining this form of treatment is a considerable undertaking, with the caveat that improvements in mobility may also occasionally render the patient at greater risk of falling or developing hallucinations. [3][4][5] The costs of LCIG are substantial, but are mitigated by improvements in quality of life years (QALY). 5 However, achieving maximal QALY relies on the durability of treatment benefit.…”
mentioning
confidence: 99%